Gynaecomastia caused by a feminizing adrenal tumour. (January 2020) - Gibbons, Stephen M; Jassam, Nuthar; Abbas, Afroze; Stuart, Kevin; Fairhurst, April; Barth, Julian H
Gynaecomastia is a common finding which typically appears during puberty in boys and in elderly males. At these times, gynaecomastia is likely to be due to physiological hormonal fluctuations, although there are a number of other causes including medications which must also be considered. We present a case of a 52-year-old male with gynaecomastia, hypogonadotropic hypogonadism and hyperoestrogenaemia. MRI of the adrenals confirmed the presence of an adrenocortical carcinoma, which after preoperative hormone workup was diagnosed as a feminizing adrenal tumour. The lesion was excised, and adjunct Mitotane therapy was commenced. Hyperoestrogenaemia is often secondary to exogenous testosterone administration; however, in the presence of hypogonadotropic hypogonadism, other sources of oestrogen should be sought. This case highlights a rare, but nonetheless important cause of gynaecomastia.